Internal erosion process and its influence factors in widely graded loose soils due to rainfall infiltration - Liang, Li; Tian, Da-Lang; Li, Zheng-Chuan (Frontiers in Earth Science, 2024)
Compared with engineering materials for earth structures subjected to prolonged, sustained hydraulic loading, the internal erosion process of widely graded loose soils (WGLS) under short-term, fluctuating hydraulic loading conditions remains insufficiently elucidated. Therefore, a novel fixed-wall permeameter is developed, capable of applying hydraulic loading at a constant flow rate and collecting effluent flowing out of specimens. A testing protocol is proposed to separate eroded silty clay particles, sandy gravel particles, and seepage water from the collected effluent. Several seepage tests are conducted on remolded specimens with various initial porosity at different inflow rates. The test results show that under a constant inflow rate, the WGLS specimens may undergo suffusion, suffosion, and stabilization stages while seeking the ultimate equilibrium state. The proposed particle migration pattern adeptly reveals the microscale mechanisms of the internal erosion phenomena observed at different stages.The inflow rate is independent of the suffusion critical hydraulic gradient but impacts the suffosion critical hydraulic gradient and internal erosion behavior following suffusion. Because hydraulic shear stress is a comprehensive indicator that considers both hydraulic gradient and initial porosity, it is more appropriate to use it to evaluate the internal stability potential of WGLS.